Perceptions of Pre-Service Technical Teachers on the Teaching and Learning Activities in Teacher Instructor Colleges of Uganda - Kintu, Denis (https://doi.org/10.37284/eajes.7.2.1913, 2024)
Understanding perceptions about the teaching and learning activities has implications on the way teacher training programs can be improved and influences trainers’ motivation. The aim of the study was to examine pre-service technical teachers’ perceptions of the teaching and learning activities in teacher-instructor colleges in Uganda. The following research questions guided the study; “Is the time allocated for the teaching and learning activities adequate; how is the tutoring conducted; are the pre-service teachers satisfied with the assignments given; do the pre-service teachers trust the teaching and learning process and are the pre-service teachers satisfied with the equipment and materials used for training? The study adopted across sectional survey design. Data was collected from 168 pre-service technical teachers using a researcher-constructed questionnaire. The data gathered was analysed using SPSS and presented as descriptive statistics. The findings revealed that time for teaching and learning; tutoring (organization of training), and assignments given were adequate; pre-service technical teachers trusted the teaching and learning process; however, they observed that the equipment and materials were inadequate for training. It was therefore recommended that the government increase the budget for technical teacher instructor institutions; lobbying for funds through; private partnerships, companies, international donor agencies, tax rebates, fellowships, and research grants to purchase adequate training equipment and engage policy makers to create mechanisms for responding to constant technology advancement for technical teacher instructor training institutions to cope